Futur et conditionnel en occitan cisalpin septentrional - Jean Sibille (Revue des Langues Romanes)
In the Occitan speaking valleys of Italy, the synthetic future and the conditional show some peculiarities, both from the point of view of morphology and use of some periphrasis of futur that compete with de synthetic future. The aim of this paper is to study these peculiarities, more particularely in the norther part of the area (occitan valleys of the Torino Province). It propose a scenario of the diferent stages of the evolution that led to the generalization of the thematic suffix -ar(i)- of the first conjugation to the other conjugations. It studies also the use of diferent forms of future. Finally, it shows that the second conditional form of the old Occitan, which has been maintained in these dialects until recently, and which does not seem to be completely out of use for the verbs "to be" and "to have", has never been exclusively specialized in the expression of the conjectural modality, contrary to what some publications seem to suggest.